The influence of joint eccentricity on the foldability of four deployable structure systems. Issue 1 (March 2022) - Pérez-Egea, Adolfo; García Martínez, Pedro; Peña Fernández-Serrano, Martino; Jiménez Vicario, Pedro Miguel; Ródenas-López, Manuel Alejandro
The study of deployable structures has been carried out traditionally by simplifying their constituent elements—joints and rods—to ideal entities. However, in this paper the dimensional thickness of these elements is taken into account, in order to evaluate their incidence on the foldability of four deployable structure systems. We have examined the eccentricity that occurs specifically at the joints themselves. Our study ultimately characterizes the incidence of this factor by defining noteworthy parameters common to both tube bundle and scissor systems, enabling us to establish a comparison and draw relevant conclusions.